PENGARUH APLIKASI KOMPOS DENGAN PUPUK ANORGANIK (NPK DAN UREA) TERHADAP POPULASI BAKTERI PELARUT FOSFAT DAN HASIL TANAMAN JAGUNG DI LAHAN KERING - P Purwanto; Yulia Nuraini; Nurul Istiqomah (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
The aim of this study was to explore the effect of a combination of manure and inorganic fertilizer (NPK and Urea) on the population of phosphate-solubilizing bacteria and the yield of maize. The study was carried out from June to October 2018 in the Kemantren Village, Alas Kulak Hamlet, Jabung District, Malang Regency. This study used a randomized block design consisting of 8 treatment levels and repeated three times. The results of the analysis of variance showed that the application of a combination of compost, fertilizer (NPK and Urea) gave significantly different results to the population of phosphate solubilizing bacteria C-organic, P-total, P-available, dry shelled weight and stover weight. The treatment of 2 t ha-1 compost + 100 kg ha-1 NPK + 50 kg gave the highest yield for the population of phosphate solubilizing bacteria with a value of 61Ã—104 CFU.g-1. Maize production yields obtained treatment of 2 t ha-1 of compost + 400kg.ha-1NPK + 200 kg.ha-1 Urea reached a value of 8.65 t ha-1.